1998
DOI: 10.1046/j.1365-2362.1998.00356.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo modifications of AcSDKP metabolism and haematopoiesis in mice treated with 5‐fluorouracil and Goralatide

Abstract: By improving our knowledge of the biology of AcSDKP in vivo during chemotherapy, our results could help to better define the therapeutic use of Goralatide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In the present study, we have found RENIN, ANGTS, and ACE I mRNA expressions in CD34+ stem cell samples of normal human subjects. ACE/CD143 was implicated in enhancing the recruitment of primitive stem cells into the S-phase by degrading AcSDKP [9,30,31,32,33]. ACE, converting Ang-I into Ang-II, is an important peptide for almost all aspects of hematopoiesis [23,31,34,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we have found RENIN, ANGTS, and ACE I mRNA expressions in CD34+ stem cell samples of normal human subjects. ACE/CD143 was implicated in enhancing the recruitment of primitive stem cells into the S-phase by degrading AcSDKP [9,30,31,32,33]. ACE, converting Ang-I into Ang-II, is an important peptide for almost all aspects of hematopoiesis [23,31,34,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…The major RAS effector agent angiotensin II (Ang II) performs its impacts on the hematopoietic system by activating the AT1Rs and AT2Rs, along with the BM microenvironment ( 11 , 12 ). As a result of ACE's (CD143) disrupting the inhibitory tetrapetide, AcSDKP, priming of stem cells into S-phase is triggered ( 16 , 21 ). Additionally, Ang-II stimulates the AT1/AT2 receptors, so it has stimulating or inhibitory effects on erythropoietin, thrombopoietin and other hematopoietic cytokines in normal hematopoiesis and myeloproliferative diseases ( 16 , 22 , 23 ).…”
Section: Local Bone Marrow Renin Angiotensin System: Definition and Amentioning
confidence: 99%
“…Therefore ACE hyperfunction may lead to the acceleration of AcSDKP metabolism, which in turn would lower its levels in the BM microenvironment, finally removing the antiproliferative effects of the peptide on haematopoietic cells and blasts. The haemoregulatory tetrapeptide AcSDKP reversibly prevents the recruitment of pluripotent HSCs and normal early haematopoietic progenitors into S-phase of the cell cycle by keeping them quiescent [14,16,34].…”
Section: Reference Evidence Proposalmentioning
confidence: 99%
“…ACE hyperfunction results in faster hydrolysis of the AcSDKP peptide, which in turn decreases in BM tissues, allowing HSCs to enter the S-stage of the cell cycle [4,16,34]. The plasma concentration of AcSDKP, a reversible negative regulator of the proliferation of normal haematopoietic stem cells, is physiologically regulated by ACE [14][15][16]121]. In vitro incubation of AML cells with an ACEI decreased the growth and colony-forming ability of AML cells in a dose-dependent manner.…”
Section: Acementioning
confidence: 99%
See 1 more Smart Citation